A catalyst-free synthesis of B, N co-doped graphene nanostructures with tunable dimensions as highly efficient metal free dual electrocatalysts. Issue 42 (7th October 2016) - Tabassum, Hassina; Zou, Ruqiang; Mahmood, Asif; Liang, Zibin; Guo, Shaojun
Abstract : A catalyst-free synthetic strategy of self-squeezing and rolling of B, N co-doped graphene nanosheets to nanotubes was reported, which exhibits tunable dimensions and atomic bonds as metal-free dual electrocatalysts by using polyethylene glycol as the directing agent.. Abstract : The search for highly efficient earth-abundant carbon nanomaterials with Pt-like electrocatalytic activity for the oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER) is still a great challenge. Herein, we present a new catalyst-free synthetic strategy of self-squeezing and rolling of B, N co-doped graphene nanosheets to nanotubes with tunable dimensions and atomic bonds as metal-free electrocatalysts for enhancing the ORR and HER using (polyethylene glycol (PEG)) as the directing agent. We found that the PEG with a higher molecular weight favors the formation of B, N co-doped graphene nanosheets with a high concentration of B–N bonds in a carbon framework whereas the one with a lower molecular weight leads to B, N co-doped graphene nanotubes (BCN nanotubes) with segregated B–C and N–C bonds. The as-prepared graphene nanostructures show interesting atomic bonds and dimension-dependent electrocatalytic activity towards the ORR and HER with BCN nanotubes being the best. The BCN nanotubes show Pt-like ORR activity and much better ORR stability than commercial Pt/C catalysts. They also exhibit excellent HER activity with a very low overpotential and a small Tafel slope of 92 mV dec −1 . The present work highlights the importance of tuning atomic bonds and dimensions of carbon nanomaterials for achieving highly efficient electrocatalysts for the ORR and HER.